2019
DOI: 10.1007/s40071-019-0224-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of apple peel extract as natural antioxidant on lipid and protein oxidation of rainbow trout (Oncorhynchus mykiss) mince

Abstract: The aim of this study was to use apple peel extract (APE) as antioxidant for inhibition of lipid and protein oxidation in rainbow trout (Oncorhynchus mykiss) mince during refrigerated storage. Apple peel extract had high 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2 0-azinobios-(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) and hydroxyl radical scavenging activity and ferric reducing antioxidant power (FRAP) comparable to ascorbic acid. Lipid oxidation was effectively inhibited in mince during 96 h of refrigerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 45 publications
1
13
0
2
Order By: Relevance
“…Recently, in 2019, Bitalebi and coworkers, studied the effect of apple polyphenols in delaying negative lipid and protein oxidation processes in rainbow trout samples during 4 days at 4 • C (Bitalebi et al, 2019). During the storage period, TBARS content increased in control samples (from 0.7 mg MDA equivalent/kg to 3.07 mg MDA equivalent/kg).…”
Section: Use Of Apple Polyphenols In Foodmentioning
confidence: 99%
“…Recently, in 2019, Bitalebi and coworkers, studied the effect of apple polyphenols in delaying negative lipid and protein oxidation processes in rainbow trout samples during 4 days at 4 • C (Bitalebi et al, 2019). During the storage period, TBARS content increased in control samples (from 0.7 mg MDA equivalent/kg to 3.07 mg MDA equivalent/kg).…”
Section: Use Of Apple Polyphenols In Foodmentioning
confidence: 99%
“…The ORAC method uses a biologically relevant free radical source (peroxyl radical), which is the most prevalent free radical in human biology [ 56 ]. Therefore, ORAC results can be correlated to in vivo studies on the antioxidant activity shown by apple polyphenols [ 57 , 58 , 59 , 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study from Muíno et al [31] described the use of an olive oil waste extract rich in polyphenols as a potential natural antioxidant applied to lamb meat patties, delaying the lipid and protein oxidation while maintaining acceptable color for a prolonged time, extending the product shelf-life to 3 days. Another recent work from Bitalebi et al [32] observed that apple peel extract (APE) Extensive research in the past few years intends to demonstrate the value of FLWas a resource of compounds with bioactivity or technological potential to introduce new, more sustainable, and natural alternatives to the market. The consumer's preferences for "clean labels" determines the use of natural compounds to replace synthetic ones, motivating the scientific community to search for new sources of natural alternatives, directing their attention to the utilization of agro-food by-products [5].…”
Section: Antioxidantsmentioning
confidence: 99%
“…A recent study from Muíno et al [ 31 ] described the use of an olive oil waste extract rich in polyphenols as a potential natural antioxidant applied to lamb meat patties, delaying the lipid and protein oxidation while maintaining acceptable color for a prolonged time, extending the product shelf-life to 3 days. Another recent work from Bitalebi et al [ 32 ] observed that apple peel extract (APE) inhibited protein and lipid oxidation in rainbow trout Oncorhynchus mykiss mince during refrigerated storage (4 °C). Furthermore, lipid oxidation was inhibited (96 h at 4 °C) lowering the peroxides and thiobarbituric acid-reactive substances (TBARS) when compared to control.…”
Section: Natural Bioactive Compoundsmentioning
confidence: 99%